Baby Bump? Birth Month, Family Income, and Early Childhood Development - Dave E. Marcotte; Katherine Engel (Institute of Labor Economics (IZA), 2023)
Federal and state tax policies in the U.S. are save families with babies born just before the end of the year thousands of dollars in tax liability. Because this income windfall is realized during the first few months of a newborn's life, we assess whether babies born in December experience developmental advantages in early childhood compared to those born right after the New Year. Using data from the Child Development Supplement of the Panel Study of Income Dynamics and the Children of the National Longitudinal Survey of Youth we implement a regression discontinuity design that exploits variation in birth timing. We show that while children born in December have a weight disadvantage of 0.17 pounds at birth compared to those born in January, they have an average weight-gain advantage of between 0.6 to 1.2 pounds (0.07 to 0.14 standard deviations) during subsequent follow-up interviews. We also find that end-of-year babies reach early developmental milestones faster, but exhibit no advantage in memory, word recognition or applied problem solving. Finally, we illustrate the tax savings received by families with end of year babies are substantial and are consistent with the end-of-year birth developmental advantage.
Keywords: J13; D1; 330; child development; income; EITC